Awareness and Utilization of Artificial Intelligence-Based Intelligent Tutoring Systems (ITS) In Enhancing Chemistry Education Through Information and Communication Technology (ICT) - Abdulmuhsin, Ibrahim; Bolaji, Hameed Olalekan; Abdulazeez, Bolanle Tawakalt-Anu; Salamia, Aishat Oyenike (ASEAN Journal of Educational Research and Technology, 2025)
This study explores the awareness and utilization of Artificial Intelligence (AI)-based Intelligent Tutoring Systems (ITS) in enhancing chemistry education through Information and Communication Technology (ICT) in Nigerian universities. Using a descriptive survey design, data were collected from 182 chemistry education lecturers across six geopolitical zones. The study assessed lecturers’ levels of awareness, accessibility, usage, and extent of integration of ITS platforms. Results revealed moderate to high awareness and a generally positive perception of ITS's value in improving teaching and learning outcomes. However, disparities in accessibility, institutional infrastructure, and practical integration hinder widespread adoption. While many lecturers acknowledged the benefits of ITS, challenges such as inadequate resources, limited institutional support, and inconsistent usage patterns remain. The study underscores the need for targeted training, institutional support, and policy reforms to facilitate the seamless adoption of ITS in chemistry education. These efforts are essential to harness the transformative potential of AI and ICT in the Nigerian higher education system.